ANALISIS BIAYA DAN WAKTU METODE HALF SLAB DALAM PEMBANGUNAN PROYEK KONSTRUKSI - Dasa Aprisandi (Program Studi Teknik Lingkungan, Fakultas Teknik, Universitas Banten Jaya, 2018)
The selection of work methods in the construction of high-rise buildings is very influential on the use of cost and time of implementation. One of the work to be done in the construction of a multi-story building is the work of the floor plate structure. The selection of appropriate floor plate method will make the construction of high rise building to be efficient. The method of execution of floor plate used in the construction of the M-Gold Tower Bekasi project is the half slab method. This method is chosen because it is more advantageous in terms of cost and time. The half slab method costs Rp. 7,985,361,365.00. with a 180-day execution time. Meanwhile, if using conventional methods cost Rp. 10,174,649,180 with a time of 300 days. So the use of the half slab method for the floor plate structure is more advantageous than using conventional method.